PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN ANDROID BERSTRUKTUR PROBLEM POSING DALAM MATERI OPERASI ALJABAR SMP - Hendri Agustriandi; Sugiatno Sugiatno; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe purpose of research is to develop learning media with android structured problem posing to improve students’ learning motivation in content of algebra operation in Junior High School. The methodology that use is a research and development. The first phase in this research is self-evaluation, in the next phase is one-to-one pilot which run in parallel with experts review. Then pilot field the last in the small group phase. Qualitative data analisys is used in the beginning phase (one-to-one and experts review), while quantitave data analisys is used in the pilot field (small group). The research results in the form of a set the learning media structured problem posing which is very valid and very feasible to be used based on the result of expert review to improve student's learning motivation. Learning media obtained deliver instructional messages in the form content of Algebra Operation in 7th grade students of Junior High School, has more than one media (multimedia) is audio and visual, load Structured problem posing at problem solving phase in media. it is interactive and independent, and increase motivation learners. Keywords: Development Research, Learning Media, Android, Problem   Posing, Motivation to Learn